Проявление межъязыковой интерференции в речевых ошибках венгерских студентов: выражение посессивных отношений - ПОВАРНИЦЫНА, МАРИНА (SlavVaria, 2021)
Cross-linguistic interference in Hungarian students’ language mistakes: representation of possessiveness. The article deals with grammatical mistakes associated with representation of possessiveness in the Russian written language of students speaking Hungarian as their native language. There are differences in representations of the possessive relation in two languages such as absence of personal possessive suffixation of names, absence of an indicator of absolute possession, the limited use of the Hungarian possessive pronouns in comparison with the Russian ones. All these form a basis for interference and cause the following mistakes: the excessive use of a possessive pronoun, nondistinction of possession and belonging meanings, wrong choice of the possessive means when expressing procedurality and locality, the excessive use of an incoordinate possessor in the form of the genitive case. Revealing of typical mistakes is aimed at their timely prevention, as well as the development of exercises to correct them.